Analysis of Langague Errors in Drafting Health Instructions in Arabic: Maternity and Children Hospital in Buraydah as an example - Al-Sultan , Muhammad Sultan Ali; Alzain, Ibrahim Abdalla Ahmed (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aims to identify language errors in the framing of Arabic health instructions at the Maternity and Children's Hospital in Buraydah, and to locate, classify, correct, and address these errors according to Arabic grammar rules. Methods: This study utilized a descriptive approach to collect and classify the selected material, as well as to study, analyze, and interpret it, in addition to highlighting incorrect and correct forms. Results: The study found that most linguistic errors are prevalent in the hospital's paper-printed health instructions. Most of these language errors relate to the fundamentals of the Arabic language taught in elementary school. The results also showed that these errors can be classified, according to linguistic study levels, into spelling, grammatical, morphological, and stylistic errors. Most of these errors arise from a lack of knowledge of basic Arabic grammar rules and confusion between Standard and Colloquial Arabic. Some errors may also result from health instructions being translated from English into Arabic and written in the translated language, while the translator is not proficient in Arabic. Recommendations: The study recommends correcting these various types of linguistic errors and writing them in clear and accurate language, preferably by having these instructions proofread before publishing.